Influence of attachment and bone loss on the mobility of incisors and canine teeth. (May 2013) - Goellner, Matthias; Berthold, Christine; Holst, Stefan; Petschelt, Anselm; Wichmann, Manfred; Schmitt, Johannes
Abstract Objective. The purpose of this clinical study was to evaluate the correlation between tooth mobility (TM), crown-to-root ratio (CRR) and clinical attachment loss (CAL) in periodontally-compromised participants. Materials and methods. While slowly biting on a load cell, the mobility of the upper incisors and canine teeth of 20 volunteers was measured using a photogrammetric measurement technique. An automated software program recorded the force-related three-dimensional TM at 3-N intervals. CAL was assessed clinically and CRR values were assessed radiographically. For each contralateral pair of teeth (central, lateral incisor, canine) and for each main level of force, the Pearson product-moment correlation coefficient between TM and CRR and between TM and CAL was computed. Correlations were considered statistically significant at p < 0.05. Results. Statistically significant positive correlations were found between TM and CRR for incisors and canines for each main level of force, whereas canines had the lowest correlation. Statistically significant positive correlations were also found between TM and CAL for the central and lateral incisors at each main level of force. Canines showed no significant correlation between CAL and TM, regardless of force level. Conclusion. The loss of attachment and bone seem to have more influence on the mobility of incisors than canines.